Private Cctv Liability Under Biometric Data Protection Rules - Muhammad Faisal Hilmi Gunawan (Riviera Publishing, 2024)
The penetration of technology that is increasingly developing has a lot of impact on human life. Increasing technology also results in the rapid development of home security equipment, especially Closed-Circuit Television cameras (hereinafter mentioned as CCTV). The right to privacy, to which everyone is entitled to personal self- protection Doctrinal legal research is a crucial aspect in recognizing various societal problems. Doctrinal research combines a systematic analysis of the provisions of legislation and the legal principles contained in it or derived from it, but also the logical and rational order of legal propositions and principles. Doctrinal legal research methods involve the analysis of legal propositions or legal concepts on which the main study is based. Case base approach demands the researcher to understand the reasons that used by the judges or another adjudicator until it reaches the final decision. Most personal data protection laws around the world distinguish between regular personal data and biometric data. At the beginning, Article 4 paragraph (1) of EU GDPR regular personal data commonly define on the laws as a set of data that able to identify a natural person either from electronic or non-electronic devices. Under the data protection laws regime especially GDPR, UK Data Protection Law and Indonesia Data Protection Law, mitigation during a data protection failure involving household CCTV systems typically involves taking immediate steps to minimize the impact of the breach Furthermore, stated in the Fairhurst v Woodard case homeowner could be held liable for failure to protect the personal data if they use camera on the outside boundary of their house and they could face hefty fine and/or tools removal. Finally, this writing contributes to undergoing discourse on cyber law field especially in data protection law and provide insights for academician, practitioner, and society.